THEME IN THE PLAYS OF GIRISH KARNA - Shabnam (International Journal of Multidisciplinary Research and Studies, 2021)
Chitra is a one-act drama that tells the narrative of Arjuna, the third Pandava, and how he came to Manipur on his travels as he was seeking to accomplish his penance. The play is based on the story of Arjuna. Here, he meets Chitrangada, the stunning daughter of King Chitravahan, who rules over this region. The king's sole child was a girl, and he had no other children who could succeed him as ruler of the realm. When Arjuna approaches the monarch to ask for Chitrangada's hand in marriage, the king presents Arjuna with a condition: the son that would be born to Chitrangada is required to be handed to the king so that he might succeed to the throne after the king's death. Arjuna gives in, and the couple eventually gets married. After some time, Chitra gives birth to a boy, at which point Arjuna departs for Hastinapur. Tagore's play, on the other hand, makes several alterations to the narrative. Chitra is portrayed in the drama as the king's fiercely independent and brave daughter. She has the ability to defend the people who serve the monarch against burglars and other criminals. She carries herself in a masculine manner and is devoid of any romantic thoughts. But all changes when she meets Arjuna, and she immediately falls in love with him. She removes the manly clothing she was wearing and transforms herself into a lovely lady so that she might woo Arjuna. Arjuna can't resist the allure she exudes. However, Chitra does not make an effort to conceal her fierce and combative nature from him. She shakes herself out of the voluptuous, soft, and timid form of beauty and finally reveals herself to Arjuna in her true form. She says to him, "and stands up straight and strong with the strength of a daring heart spurning the wiles and arts of twining weakness if I hold my head high like a tall young mountain fir...would she then appeal to a man's eye?" She goes on to ask him if she would then appeal to a man's She is not a deity and should not be worshipped; she is simply Chitra. Arjuna has no problem acknowledging her in her true, original form.